JOB SATISFACTION AS A MEDIATOR OF EFFECT JOB STRESS AND CAREER DEVELOPMENT ON EMPLOYEE TURNOVER INTENTION PT PKSS - Pratiwi, Fitriani; Johannes Singmin Lo (Dinasti Publisher, 2020)
This study aims to examine and analyze the Effect of Job Satisfaction as a mediator variable Job Stress and Career Development on PT PKSS Employee Turnover Intention. This type of research used in this study is quantitative. Samples are calculated using the saturated sample method. The subjects of this study were 98 PT PKSS head office employees. Data were analyzed using Path Analysis with the help of Smart PLS. The results of this study show that (1) Job Stress has a significant negative effect on Job Satisfaction; (2) Career Development has a significant positive effect on Job Satisfaction; (3) Job Stress has a significant positive effect on Turnover Intention; (4) Career Development has a significant positive effect on Turnover Intention; (5) Job Satisfaction mediates Job Stress and Career Development towards Turnover Intention.